(untitled) (Journal of the College of Basic Education, 2022)
Hybrid system based on photovoltaic is considered an effective option to electrify remote and isolated areas far from grid. This is true for areas that receive high averages of solar radiation annually. Using diesel generator as a standby source will make utilization of hybrid systems more attractive. An economic feasibility study and a complete design of a hybrid system consisting of photovoltaic (PV) panels, a diesel generator as a backup power source and a battery system supplying a small community in Baghdad were presented in this paper. Specifications of the hybrid system components are then determined according to the optimized values. A new concept in power generation is a micro-grid. A micro-grid involves connecting several small alternative power sources in addition to the main grid on a particular site. Some examples where it could be used would be an offices, houses , industrial site or shopping centre. Little is known about micro-grid behavior on the whole. Some models exist which describe the components of a micro-grid, although to date a successful model of an entire micro-grid system has not been developed. Two areas were chosen to do this research . Currently models of a photovoltaic array, a wind turbine and a gas turbine have been developed. These are connected to a load and the mains power supply